A method for catalyzing graphitization of petroleum calcined coke and its application
By using petroleum calcined coke and catalyst for graphitization, the problems of slow charge and discharge rate and low specific capacity in the preparation of graphite anode materials for lithium-ion batteries are solved, and the preparation of high-performance artificial graphite materials is realized, which is suitable for lithium-ion batteries.
Patent Information
- Application Number
- CN202310262828.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The preparation of graphite anode materials for existing lithium-ion batteries has problems such as slow charge and discharge rates, low specific capacity, and reduction of organic solvents, which limit the application of graphite.
The petroleum calcined coke is used as the precursor, and graphitization is achieved by adding metal element or oxides and carbides as catalysts, ball milling and high-temperature heating treatment.
It effectively shortens the graphitization time and improves the graphitization yield. The artificial graphite produced has high specific capacity, high rate performance and good cycle stability, and is suitable for lithium-ion battery negative electrode materials.
Smart Images

Figure CN116514118B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial graphite materials, and in particular to a method for catalyzing graphitization of petroleum calcined coke and its application. Background Art
[0002] Negative electrode material is one of the key components of lithium-ion batteries. Graphite has become the most widely used negative electrode material in commercial lithium-ion batteries because of its advantages such as good electrical conductivity, chemical stability and structural stability, and its low cost and wide availability. However, the layered structure of graphite limits the charge transfer process, resulting in a slow charge and discharge rate, which limits the power density and rate performance of the battery. In addition, problems such as low specific capacity and organic solvent reduction also limit the application of graphite. In order to solve these problems, it is necessary to prepare graphite negative electrode materials with high capacity, high rate performance and stable cycle performance.
[0003] According to different sources, graphite can be divided into natural graphite and artificial graphite. Compared with natural graphite, artificial graphite has a wide range of sources, fewer impurities and defects, and has become the main source for preparing lithium-ion negative electrode materials. Artificial graphite is made from some carbon materials that can be graphitized under high temperature conditions. It can be made from needle coke, asphalt coke, mesophase carbon microspheres, asphalt, etc. At present, most artificial graphite is produced from needle coke. In recent years, needle coke has been in short supply and its price has continued to rise, which has led to an increase in the cost of lithium-ion batteries. Wang Jin et al., in "Artificial graphite microspheres for preparing lithium-ion battery negative electrodes and preparation methods thereof" (CN101880042A), graphite microspheres were prepared using asphalt and other raw materials. The degree of graphitization was high, but the process was cumbersome and the process was complicated. Liu Chunyang et al., in "Artificial graphite negative electrode material, preparation method thereof and lithium ion negative electrode" (CN108383116A), used needle coke and other raw materials for granulation and carbonization to produce artificial graphite with good rate performance, but its graphitization degree was low.
[0004] In summary, the preparation of graphite negative electrode materials for lithium-ion batteries is a field that has attracted much attention. Finding an artificial graphite that is easy to prepare, low-cost and has good performance has important research significance and application value. Summary of the invention
[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a method and application of catalytic graphitization of petroleum calcined coke, using petroleum calcined coke as a precursor, and using metal elements or oxides, carbides as catalysts in the graphitization process. The present invention can effectively shorten the graphitization time, increase the graphitization yield, and is easy to control, and does not use toxic and harmful substances. Therefore, the present invention has good application prospects and economic benefits, and has the potential for industrial production.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for catalyzing graphitization of petroleum calcined coke comprises the following steps:
[0008] Step 1: Prepare petroleum calcined coke precursor powder of appropriate particle size;
[0009] Step 2: Adding an appropriate amount of catalyst to the precursor powder to form a mixture to promote graphitization;
[0010] Step 3: Fully mix the precursor and catalyst by ball milling;
[0011] Step 4: Heat the mixture to a high temperature in an oxygen-free inert atmosphere and keep it warm for a certain period of time to obtain an artificial graphite negative electrode material.
[0012] In the step 1, the sizes of the petroleum calcined coke precursor powders are different, with an average particle size of 1 to 10 μm.
[0013] The catalyst in step 2 is Fe, Co, Ni, Fe 2 O 3 、Al 2 O 3 , B 2 O 3 , B 4 C, SiC, SiO 2 One or more of a single substance or compound.
[0014] In the step 2, the mass percentage of the catalyst in the mixture is 2% to 30%.
[0015] The ball milling apparatus in step 3 is a planetary ball mill, the grinding beads are stainless steel balls, the ball milling time is 1 to 3 hours, the ball-to-material ratio is 10:1 to 5:1, and the rotation speed is about 450 rpm, so that the precursor and the catalyst are fully mixed.
[0016] In the step 4, the graphitization temperature is 2200-3000° C., the holding time is 1 h-3 h, and the protective atmosphere is argon, so that the precursor is fully graphitized at high temperature.
[0017] The artificial graphite negative electrode material has smooth and flat crystal surfaces and clear graphite lattice stripes.
[0018] The raw materials and experimental reagents used in the present invention are all commercially available.
[0019] The artificial graphite negative electrode material prepared by the method of catalyzing graphitization of petroleum calcined coke is applied to the negative electrode of lithium ion battery.
[0020] Beneficial effects of the present invention:
[0021] (1) The artificial graphite prepared by the present invention has a flat surface and a regular shape, and the spacing between graphite flakes is about 0.356 nm, which is close to ideal graphite.
[0022] (2) The precursor used is petroleum calcined coke, which has lower cost than needle coke, the main raw material for producing artificial graphite.
[0023] (3) The catalytic graphitization route used in the present invention is simple. The traditional graphitization method is complicated, takes a long time, has low production efficiency, and the graphitization degree of the obtained graphite material is low. The addition of the catalyst greatly promotes the reaction, shortens the graphitization time, and the graphitization process is easy to control and can be industrialized.
[0024] (4) The catalyst used in the present invention has a significant catalytic effect on the graphitization process and can reduce the temperature and insulation time required for graphitization. The graphitization degree of the obtained calcined coke-based graphite is significantly improved.
[0025] (5) The calcined coke-based graphite obtained is used as the negative electrode material of lithium-ion batteries, showing excellent specific capacity, rate performance and cycle performance. The charge and discharge performance under various current sizes is improved. At a current of 0.1C, its charge specific capacity can reach about 370mAh / g, which is close to the theoretical specific capacity of graphite. Even at high currents of 2C and 3C, the charge specific capacity can reach 311mAh / g and 283mAh / g. And it can maintain good cycle stability in long cycles. After 200 cycles, the capacity loss is less than 2%, and the lost capacity is very low. In summary, the artificial graphite obtained by the present invention has very obvious performance advantages over commonly used commercial graphite, and its application prospects are very broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The following is the XRD spectrum of the artificial graphite material prepared in the present invention.
[0027] Figure 2 This is the first cycle charge and discharge curve of the artificial graphite negative electrode material prepared in Example 2.
[0028] Figure 3 This is a cycle performance diagram of the artificial graphite negative electrode material prepared in Example 3.
[0029] Figure 4 This is a rate performance diagram of the artificial graphite negative electrode material prepared in Example 4.
[0030] Figure 5 These are the SEM and TEM images of the artificial graphite material prepared in Example 5.
[0031] Figure 6 This is a rate performance diagram of the artificial graphite negative electrode material prepared in Example 6. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with embodiments.
[0033] The present invention provides a method for preparing a petroleum calcined coke-based artificial graphite negative electrode material, comprising the following steps:
[0034] Step 1: Prepare petroleum calcined coke precursor powder of appropriate particle size.
[0035] Calcined petroleum coke is a low-cost carbon material, about half the cost of needle coke, with a high carbon content and few impurities, making it a very promising negative electrode material. However, calcined petroleum coke contains some amorphous carbon that is difficult to graphitize, resulting in the artificial graphite made from calcined petroleum coke having a lower crystallinity than needle coke. When it is used as a negative electrode material for lithium-ion batteries, it is difficult to meet the market's requirements for high performance, which limits the further application of calcined petroleum coke. In order to overcome this shortcoming, it is necessary to increase the graphitization degree of calcined petroleum coke in a simple and low-cost way.
[0036] For example, the average particle size ranges from about 1 to 10 μm.
[0037] Step 2: Add an appropriate amount of catalyst to the precursor powder to form a mixture to promote graphitization.
[0038] In the embodiment of the present invention, the catalyst can be Fe, Co, Ni, Fe 2 O 3 、Al 2 O 3 , B 2 O 3 , B 4 C, SiC, SiO 2 One or more of the simple substances or compounds. The amount of catalyst added is 2% to 30% of the mixture by mass.
[0039] Step 3: Mix the precursor and catalyst thoroughly by ball milling.
[0040] In the embodiment of the present invention, a planetary ball mill is used as the ball milling apparatus, stainless steel balls are used as grinding beads, the ball milling time is 1 to 3 hours, the ball-to-material ratio is 10:1 to 5:1, and the rotation speed is 450 rpm.
[0041] Step 4: Heat the mixture to a high temperature in an oxygen-free inert atmosphere and keep it warm for a certain period of time to obtain an artificial graphite negative electrode material
[0042] In the embodiment of the present invention, the oxygen-free inert atmosphere is an argon atmosphere, and the heating parameters are 2200-3000° C. for 1 h to 3 h.
[0043] According to the above process, the principle of the present invention is to reduce the reaction energy barrier by adding a catalyst, thereby reducing the temperature required for the graphitization reaction and increasing the graphitization degree of the product. Petroleum calcined coke is a soft carbon with disordered atomic distribution. After being heated to a high temperature in an oxygen-free atmosphere, the thermodynamically unstable carbon atoms move and rearrange, and the crystals grow to form graphite with a highly ordered structure. The resistance of this solid-phase reaction is large and it is easy to form a metastable state. The catalyst can dissolve carbon. When the disordered carbon reaches solubility in the catalyst, some of the dissolved carbon atoms tend to transform into low-energy graphite and precipitate, thereby promoting the graphitization process.
[0044] Example 1: The present invention provides a catalytic graphitization method for petroleum calcined coke to improve graphitization degree and lithium storage performance, comprising the following steps: preparing a calcined coke precursor powder with an average particle size of about 2 μm (calcined coke carbon content> 98.5%), adding 8% by mass of Fe 2 O 3 The powder was put into a ball mill for 1 h to be fully mixed (the grinding beads were steel balls, and the ball-to-material ratio was 10:1). 2 O 3 The mixture is put into a crucible, placed in a vacuum graphitization furnace, and heated to 2800℃ at 35℃ / min in an argon atmosphere and kept warm for 2h. Artificial graphite material can be obtained. XRD test spectrum ( Figure 1 ) showed diffraction peaks corresponding to typical crystal planes of graphite crystals, indicating that the obtained petroleum calcined coke-based graphite has a high degree of crystallinity and is free of other impurities. The calculated graphitization degree is 95.5%, which is significantly higher than that of petroleum calcined coke, indicating that the addition of the catalyst promotes the graphitization process of petroleum calcined coke.
[0045] Example 2: This example differs from Example 1 in that 8% Si powder is added to the precursor, and the rest is the same as Example 1. The prepared artificial graphite is used as the negative electrode material of lithium-ion battery to assemble button batteries, and constant current charge and discharge tests are carried out in the battery test channel. The first cycle charge and discharge curve is as follows: Figure 2 As shown, the addition of the catalyst significantly improved the first charge specific capacity, and the specific capacity at 0.1C reached 369 mAh / g, which is close to the theoretical specific capacity of graphite.
[0046] Example 3: This example is different from Example 1 in that 8% by mass of SiC powder is added to the precursor, and the rest is the same as Example 1. Figure 3The rate performance test shows that after adding the catalyst, the specific capacity of the artificial graphite negative electrode material at different current sizes has increased, showing good rate performance. The specific capacity at 0.1C is increased to 365mAh / g, and at 3C, the charging specific capacity can reach 283mAh / g, which is more than 50% higher than that of artificial graphite without adding catalyst. This shows that the addition of the catalyst improves the rapid charging and discharging ability of the graphite material.
[0047] Example 4: This example differs from Example 1 in that 8% Co powder is added to the precursor, and the rest is the same as Example 1. The obtained artificial graphite negative electrode material is subjected to a cycle performance test, and the results are as follows: Figure 4 As shown, the artificial graphite obtained by catalytic graphitization exhibits good cycle stability, with almost no capacity decay after 100 cycles, and the capacity retention rate can be maintained at around 90% even after 300 cycles.
[0048] Example 5: This example is different from Example 1 in that 8% Ni powder is added to the precursor, and the rest is the same as Example 1. The obtained artificial graphite material is observed by scanning electron microscope and transmission electron microscope to obtain its microscopic morphology, as shown in FIG. Figure 5 As shown. From the SEM image in Figure (a), it can be seen that smooth and flat crystal surfaces appeared in the catalytic petroleum calcined coke, which shows that the catalyst promotes the graphitization process of the calcined coke. In the TEM image in Figure (b), clear graphite lattice fringes can be seen. After measurement and calculation, the interlayer spacing of graphite sheets is about 0.356nm, which is close to the interlayer spacing of ideal graphite crystals, which shows that the graphitization degree of the calcined coke has been significantly improved.
[0049] Example 6: This example is different from Example 1 in that the average particle size of the calcined coke precursor powder is 8 μm, and the rest is the same as Example 1. The measured rate performance is as follows: Figure 6 As shown, the specific capacity of artificial graphite with large particle size is reduced, and the rate performance can be improved by catalytic graphitization. The specific capacity of artificial graphite obtained without using a catalyst at 3C is about 140mAh / g, while the graphite negative electrode material obtained by catalytic graphitization can reach more than 220mAh / g at the same current size.
[0050] The present invention uses a new catalyst to catalyze graphitization of petroleum calcined coke, which can effectively shorten the graphitization time, improve the graphitization yield, and is easy to control, and does not use toxic and harmful substances. Therefore, the present invention has good application prospects and economic benefits, and has the potential for industrial production. Matters not covered by the present invention are known technologies.
Claims
1. A method for catalyzing graphitization of petroleum calcined coke, characterized in that: The steps include: Step 1: Prepare petroleum calcined coke precursor powder of appropriate particle size; Step 2: Adding an appropriate amount of catalyst to the precursor powder to form a mixture to promote graphitization; Step 3: Fully mix the precursor and catalyst by ball milling; Step 4: heating the mixture to a high temperature in an oxygen-free inert atmosphere and keeping the temperature for a certain period of time to obtain an artificial graphite negative electrode material; The surface of artificial graphite is flat and regular in shape, and the spacing between graphite flakes is 0.356nm; In the step 1, the size of the petroleum calcined coke precursor powder varies, with an average particle size of 1 to 10 μm; The catalyst in step 2 is one or more of Fe, Co, Ni, Fe2O3, Al2O3, B2O3, B4C, SiC, SiO2 single substances or compounds.
2. A method for catalyzing graphitization of petroleum calcined coke according to claim 1, characterized in that: In the step 2, the mass percentage of the catalyst in the mixture is 2% to 30%.
3. A method for catalyzing graphitization of petroleum calcined coke according to claim 1, characterized in that: In the step 3, the ball milling apparatus is a planetary ball mill, the grinding beads are stainless steel balls, the ball milling time is 1 to 3 hours, the ball-to-material ratio is 10:1 to 5:1, and the rotation speed is 450 rpm.
4. A method for catalyzing graphitization of petroleum calcined coke according to claim 1, characterized in that: In the step 4, the graphitization temperature is 2200-3000° C., the insulation time is 1 h-3 h, and the protective atmosphere is argon.
5. A method for catalyzing graphitization of petroleum calcined coke according to any one of claims 1 to 4, characterized in that: The artificial graphite negative electrode material prepared by the method of catalyzing graphitization of petroleum calcined coke is applied to the negative electrode of lithium ion battery.
Citation Information
Patent Citations
Artificial graphite microspheres for preparing cathode of lithium ion battery and preparation method thereof
CN101880042A
Artificial graphite negative electrode material and preparation method thereof as well as lithium-ion battery negative electrode
CN108383116A
Artificial graphite material with spherical structures and preparation method thereof
CN110655073A
Cited By
Catalytic graphitization method and application
CN121778722A